FY2016 : Output Cost Estimates and Budget Outturn Paper. (Policy Papers; Policy Paper ;, 2016)
Operating within a flat real budget envelope, the Fund delivered on the priorities and initiatives laid out in the Global Policy Agenda and Management's Key Goals (MKGs). Resource pressures were addressed via implementation of streamlining initiatives, strategic reallocation of resources towards higher priority areas, and careful budget management. In terms of outputs, spending in FY 16 continued the shift from crisis management to crisis prevention, in line with the MKGs. Output shifted moderately from multilateral surveillance and oversight of the global system to bilateral surveillance and capacity development. Lending activity expenditure remained broadly unchanged. Average country spending was broadly aligned with assessment of risk. The net administrative budget outturn in FY 16 was USD 1,038 million against an approved budget of USD 1,052 million. The modest underspend reflects the preservation of the contingency reserve and lower-than-planned travel expenditure. Relative to FY 15, higher budget execution led to a small real (0.8 percent) year-on-year increase in net expenditures. Total capital expenditures of USD 131 million were recorded in FY 16 out of the USD 435 million in available appropriations. HQ1 Renewal expenses made up 70 percent of the spending.